Patient after liver transplantation due to hepatic cirrhosis from a deceased donor – nursing interventions based on case report - Łój, Dominika; Maj, Natalia; Piątek, Tomasz; Małkowski, Piotr (Pielęgniarstwo Chirurgiczne i Angiologiczne/Surgical and Vascular Nursing, 2020)
Liver cirrhosis is the end stage of chronic liver diseases, leading to organ failure, the only possible treatment of which is liver transplantation. Liver transplantation is one of the most difficult surgical procedures, and it bears the possibility of complications. Hence, the special role of nursing staff in caring for the recipient. The aim of the study was to present nursing interventions on the example of two female patients after liver transplantation. The first patient was transplanted due to liver cirrhosis of unknown aetiology, and the second patient had liver cirrhosis following hepatitis C virus. Nursing interventions were conditioned by nursing problems and they differed slightly between the described cases. The presented nursing interventions are typical procedures for the group of liver recipients and specific for the described cases.